Primary hepatic squamous cell carcinoma: case report and systematic review of the literature - Zhao, Lin; Zhou, Yan; Ding, Jianmin; Qin, Zhengyi; Zhou, Hongyu; Jing, Xiang (Frontiers in Oncology, 2023)
Primary hepatic squamous cell carcinoma (SCC) is extremely rare and only a few dozen cases have been reported to date, and it can barely be diagnosed before histopathological examination, which necessitates exclusion of metastatic tumors. In this case, we present a 60-year-old female patient with no comorbidity, as laboratory tests and imaging examinations were not diagnostic, ultrasonography (US)-guided liver biopsy was performed and eventually revealed a definitive pathological diagnosis of hepatic SCC. After excluding metastasis, the diagnosis of primary hepatic SCC was established, then chemotherapy and immunotherapy were performed. Additionally, we conducted a comprehensive literature search on primary hepatic SCC using PubMed, Google Scholar, and Web of Science, and a total of 53 articles were retrieved with a time range from 1972 to 2022. A critical analysis was then performed to evaluate previous literatures focusing on the clinical characteristics, imaging features, treatments, and prognosis.